Effects of implementing herd health programme on performance of goats in a smallholder farm - Shahudin, Muhammad Syafiq (2017)
Most of goat farms owned by smallholders in Malaysia were not managed to the expectation due to unavailability of information in good management practice for goat. Indeed, low performance of goats with respect to the growth performance, feed utilization, disease resistance, reproductive efficiency and meat and milk production was associated to improper rearing protocol specifically on herd health programme. This study was carried out to introduce a proper herd health programme for smallholder goat farm in order to enhance the farm production. This study was conducted at a smallholder goat farm in Negeri Sembilan, where initially, screening programme was done to analyze the common herd problems in the farm in term of feeding, health and breeding management problems. Then, formulation and implementation of herd health programme was done, where 60 female Boer cross goat aged 4 month old and approximately weighing about 20 kg were selected and divided into two groups; control: animals were managed according to the current practice by the farmer which has never been practice herd health programme and experimental group: animals were managed by implementing a proper herd health programme. The herd health programme given to the experimental group included feeding, vaccination, deworming, bio security and breeding programme. Throughout the study, gradual health screening programme was performed for goats in both groups at every 3 months by collecting blood, faecal and nasal swab samples. The goats were put in respected pen until reached suitable age and weight for breeding, which was 1 year old and 30 kg body weight respectively. The study was started in January 2015 and ended a year later. After 5 months of feeding programme, the mean of final body weight in experimental group (28.8±0.87 kg) has shown a significant improvement compared with control group (25.6±0.81 kg). Thirteen goats in the experimental group also had successfully achieved ideal body condition score with the score of 3 (86.7%), compared to only 9 goats (60%) in control group, where the score was below 3. In term of health performance, at the end of the study, the percentage of disease occurrence was significantly (p<0.05) higher in control group as compared to experimental group, where in October 2015 (last screening program), pneumonic mannheimiosis cases observed in control group was 27 cases compared to experimental group which was 2 cases. For coccidiosis, the number was high in control group (21 cases) as compared to experimental group (1 case). Colibacillosis was also high in control group (23 cases) as compared to experimental group (2 cases). Lastly for mycoplasmosis, there were 13 cases observed in control group as compared to experimental group, 5 cases. In accordance with decreasing number of disease occurrence, the mortality rate among female breeder goats was also higher in control group (16.67%) as compared to experimental group (3.33%) throughout the year. In term of breeding performance, there was significantly (p<0.05) increased of pregnancy rate up to 86.7%, in experimental group, as compared to 33.3% in control group. Out of 86.7% of pregnant does in experimental group, 35% of the pregnant does showed twins whereas there was no twin reported in the control group. As for kidding rate, it had significantly (p<0.05) increased up to 100% in experimental group, as compared to 70% in control group. Lastly, there was also an improvement in the weaning rate in the experimental group, which the weaning rate was 100%, significantly higher as compared to control group which was 57.1%. In conclusion, this study has shown that the implementation of herd health programme in smallholder goat farm can improve the performance of the goats in term of growth, disease resistance and breeding performance. Thus, herd health programme which consist of different components such as disease prevention, feeding, bio security and breeding programme is indeed a crucial program to be practiced by smallholder goat farm.